Healthcare-associated infections caused by Candida spp. in critical infants: a look at environmental surfaces - Priscila Guerino Vilela; Isadora Caixeta da Silveira Ferreira; Ralciane de Paula Menezes; Mário Paulo Amante Penatti; Reginaldo dos Santos Pedroso; Denise Von Dolinger de Brito Röder (Revista de Epidemiologia e Controle de Infecção)
Background and Objectives: invasive fungal infections entail high morbidity and mortality rates in Neonatal Intensive Care Units (NICUs) and are accompanied by an increasing prevalence of resistant isolates, highlighting hospital environments as the primary sources of contamination. This study identified Candida species in infants in a Brazilian NICU, assessed their clinical and laboratory conditions and characterized the isolates. Methods: Candida isolates from newborns (NBs) and environments were identified and analyzed for antifungal resistance, virulence factors, and molecular relationships. Results: four NBs presented invasive candidiasis, such as C. albicans (2 NBs), C. glabrata (1 NB), and C. parapsilosis sensu stricto (1 NB). All NBs were extremely premature (<29 weeks) and had used at least one invasive device. Two clinical isolates demonstrated resistance, one to fluconazole (C. parapsilosis sensu stricto) and the other to micafungin (C. glabrata). Five environmental isolates were identified as C. parapsilosis sensu stricto, and one of them showed to be fluconazole susceptible-dose dependent. Biofilm was the only virulence factor produced by all nine isolates. Molecular analysis revealed high similarity between one environmental isolate and one clinical isolate of C. parapsilosis sensu stricto. Conclusions: the results indicated the presence of Candida species in infants and NICU environments, with some demonstrating in vitro resistance to fluconazole and micafungin. All isolates produced biofilm. A notable genetic similarity was observed between some environmental and clinical isolates, suggesting the environment as a possible source of infection.